Beneficial effects of tyrosol on altered glycoprotein components in streptozotocin-induced diabetic rats - Ramasamy Chandramohan; Settu Saravanan; Leelavinothan Pari (Taylor & Francis Group, 2017)
Context: Olive oil is the major source of tyrosol which is a natural phenolic antioxidant. Olive oil constitutes a major component of the Mediterranean diet that is linked to a reduced incidence of chronic diseases. Objective: This study evaluates the effects of tyrosol on altered glycoprotein components in streptozotocin-induced diabetic rats. Materials and methods: Diabetes mellitus was induced in male Wistar rats by streptozotocin (40 mg/kg body weight). These rats were administered tyrosol (20 mg/kg body weight) and glibenclamide (600 μg/kg body weight) orally daily for 45 days. Plasma glucose, plasma insulin, glycoprotein components such as hexose, hexosamine, sialic acid and fucose in the plasma, liver and kidney, and histopathogy of tissues were analyzed. Results: Diabetic rats revealed significant (p < 0.05) increase in the levels of glucose, hexose, hexosamine, sialic acid and fucose (277.17, 152.45, 100.43, 79.69 and 49.29 mg/dL) in the plasma; decrease in the levels of palsma insulin (6.12 μU/mL) and sialic acid (4.36 and 5.03 mg/g) in the liver and kidney; significant (p < 0.05) increase in hexose (49.33 and 46.82 mg/g), hexosamine (22.68 and 33.20 mg/g) and fucose (31.63 and 32.44 mg/g) in the liver and kidney. Further, periodic acid-Schiff staining of tissues revealed positive-stain accumulation in diabetic rats. Tyrosol treatment showed significant (p < 0.05) effects on all the biochemical parameters and histopathology studied in streptozotocin- nduced diabetic rats. Also, the in vitro study revealed the antioxidant effect of tyrosol. Discussion and conclusions: Thus, tyrosol protects streptozotocin-induced diabetic rats from the altered glycoprotein components. Further, this study can be extrapolated to humans.